Self-efficacy in sport - Feltz, Deborah L.; Short, Sandra E.; Sullivan, Philip Joseph 1969- (Champaign, IL Human Kinetics, 2008)
This book provides a reference for sport psychology lecturers, students, coaches and other professionals with an interest in the field. Self-belief, known as 'self-efficacy' by sports psychologists is widely believed to be an essential component of sporting success. This book examines the nature of efficacy as it applies to sporting behaviour in coaches, athletes and teams. It is the first reference book entirely devoted to the concept of self-efficacy in sport. It provides readers with a basic background of research on the topic, as well as current and future trends; offers research-tested guidelines and recommendations for using efficacy techniques with individual athletes and teams; and, includes a comprehensive annotated bibliography of references on the topic
Part 1. Understanding self-efficacy theory. Self-efficacy theory in sport -- Measuring efficacy beliefs -- Part 2. The nature of efficacy beliefs in athletes, teams, and coaches. Efficacy beliefs of athletes -- Efficacy beliefs of teams -- Efficacy beliefs of coaches -- Part 3. Building, maintaining, and regaining efficacy beliefs in sport. Enhancing efficacy beliefs of athletes -- Enhancing efficacy beliefs of teams -- Enhancing efficacy beliefs of coaches -- Future directions for research on efficacy beliefs
Includes bibliographical references and index
Keywords: Success; Athletes -- Psychology; Coaching (Athletics) -- Psychological aspects; Sports -- Psychological aspects; Sports teams -- Psychological aspects